Effect of reverse logistics to the organization performance - Lim, Jit Liang; Aziz, Zulkufli (2012)
Reverse Logistics is the process of return that supposed excess inventories, customer returns and seasonal product. The main purpose of the research focuses on develops knowledge about how the reverse logistics effects the organization performance.In this research, we also briefly discuss the benefits and process of the reverse logistics. The research methodology in the research is focus on secondary data which refer to the journal and internet resources.As conclusion, the research founded that reverse logistic is very significant to the organization performance.